CANNABIS FOR HEALTH - Dwi Septian Wijaya (Journal of Holistic and Traditional Medicine, 2021)
Cannabis (cannabis, marijuana) is an addictive substance. About 5,000 years ago, China used as a medicine. Cannabis or hemp comes from a plant called Cannabis sativa. This plant has 100 different chemical substances called cannabinoids. Each ingredient has a different effect on the body. Cannabis is divided into three types, namely Cannabis sativa, Cannabis indica and Cannabis ruderalis. These three types of cannabis contain different levels of tetrahydrocannabinol (THC). This drug derived from cannabis leaves contains Tetrahydrocannibinol (THC), one of 400 chemicals that can cause mood swings. tetrahydrocannabinol (THC) and cannabidol (CBD) are the main chemicals that are often used in medicine.